2011
DOI: 10.4142/jvs.2011.12.2.191
|View full text |Cite
|
Sign up to set email alerts
|

A simplified PCR assay for fast and easy mycoplasma mastitis screening in dairy cattle

Abstract: A simplified polymerase chain reaction (PCR) assay was developed for fast and easy screening of mycoplasma mastitis in dairy cattle. Species of major mycoplasma strains [Mycoplasma (M.) bovis, M. arginini, M. bovigenitalium, M. californicum, M. bovirhinis, M. alkalescens and M. canadense] in cultured milk samples were detected by this simplified PCR-based method as well as a standard PCR technique. The minimum concentration limit for detecting mycoplasma by the simplified PCR was estimated to be about 2.5 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Recently, an improved PCR buffer was developed to neutralize these inhibitory substances in whole blood [2]. Direct PCR performed using this improved buffer has been shown to demonstrate superior sensitivity [2,9]. In the present study, we analyzed 49 samples by direct and standard PCR and found that the sensitivity of direct PCR was 10-fold higher than standard PCR.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, an improved PCR buffer was developed to neutralize these inhibitory substances in whole blood [2]. Direct PCR performed using this improved buffer has been shown to demonstrate superior sensitivity [2,9]. In the present study, we analyzed 49 samples by direct and standard PCR and found that the sensitivity of direct PCR was 10-fold higher than standard PCR.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, direct PCR assays for hemoparasites, such as Babesia gibsoni, and hemoplasma species using whole blood of dogs and cats have been developed to reduce time, cost and labor and to eliminate contamination risks [31,33]. Moreover, direct PCR was also used in a large-scale epidemiological study for bovine mastitis caused by Mycoplasma infection as a faster, easier method of screening [9]. Therefore, it is thought that a direct PCR method can also detect bovine hemoplasma infections and is suitable for largescale investigation.…”
mentioning
confidence: 99%
“…Several researches demonstrated that sampling by BALF was more useful for prediction of lower respiratory airway pathogens than nasal swabs although clearly not as convenient [19,20]. Therefore, in this study, PCRs based on 16S rRNA genes amplified M. bovis DNA [15,21] and were used to confirm Mycoplasma bronchopneumonia, using BALF samples.…”
Section: Discussionmentioning
confidence: 98%
“…Sub-samples were cultivated and investigated by polymerase chain reaction (PCR) tests targeting the M. bovis, based on 16S rRNA genes [15]. Briefly, simplified PCR was performed in a total reaction volume of 20 μL containing 10 μL of 2× AmpdirectPlus (Shimadzu Co., Kyoto, Japan), 0.5 U of Nova taq TM Hot Start DNA polymerase (Novagen, UK), 5 pmol of a mycoplasma universal primer set (MycoAce; Nihon Dobutsu Tokusyu Shindan Ltd., Hokkaido, Japan), and 5 μL of each samples.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR for Mollicutes using bronchoalveolar lavage fluid detected Mycoplasma bovis in 1 sample (5%) from an apparently healthy calf and in 21 samples (100%) from calves with bronchopneumonia. 2 Therefore, the statistical analysis focused on 19 healthy controls in which Mycoplasma bovis had not been detected and 21 calves with bronchopneumonia. A volume of 4 mL of whole blood was collected via jugular venipuncture into heparinized tubes for endotoxin and cTnI analyses and centrifuged at room temperature within 15 minutes of collection.…”
Section: Ear Editormentioning
confidence: 99%